Community Awareness and Social Norms in Household Waste Management: A Qualitative Study in Tanjung Unggat Coastal Settlement - Marsya Adriana; Rosa Efani; Riska Milia Sari; Sri Wahyuni (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
Household waste management remains a persistent environmental issue in Indonesia's coastal communities, where inadequate disposal practices threaten environmental sustainability and public health. This qualitative descriptive study examines the cognitive, affective, and behavioral dimensions of community awareness and the role of social norms in household waste management in the Tanjung Unggat coastal settlement, Tanjungpinang City. Data were collected through non-participant observation, semi-structured in-depth interviews, and documentation. Eight informants were selected purposively, consisting of five coastal residents, one community leader, one village government representative, and one sanitation officer. The findings show that residents generally understand the environmental and health risks of unmanaged waste and express concern about coastal cleanliness, but behavioral commitment remains inconsistent. Direct disposal into coastal waters and open burning persist because they are normalized through long-standing neighborhood practices and reinforced by limited facilities and irregular collection services. Drawing on Émile Durkheim's concept of collective consciousness, the study demonstrates that household behavior is shaped by shared norms and social expectations rather than by individual awareness alone. Sustainable improvement therefore requires coordinated infrastructure, continuous environmental education, community participation, and reinforcement of pro-environmental local norms.